2018
DOI: 10.5530/jyp.2018.10.45
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Predisposing Factors Associated with Suspected Adverse Drug Reactions of Hospitalized Patients

Abstract: Objectives: To study the incidence and to evaluate the risk factors of suspected adverse drug reactions developed in the hospitalized patients of various departments and to assess the causality and severity of adverse drug reactions (ADRs). Methods: It was a retrospective-prospective study conducted in a tertiary care hospital for a period of two years two months, with a specific predefined criterion. A total of 254 subjects with ADRs were identified during the period of study for which 1:1 ratio of subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
1
4
0
6
Order By: Relevance
“…This is primarily because of the reason that the risk of drug interactions increases when more number of drugs are prescribed to the patients which leads to the development of ADEs [ 65 ]. Similar to findings of previously published studies [ 66 68 ], a significant association was found in current study between male gender and ADEs. In contrast to this, other studies depict that antibiotics associated ADEs are more commonly found among females as compared to males [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is primarily because of the reason that the risk of drug interactions increases when more number of drugs are prescribed to the patients which leads to the development of ADEs [ 65 ]. Similar to findings of previously published studies [ 66 68 ], a significant association was found in current study between male gender and ADEs. In contrast to this, other studies depict that antibiotics associated ADEs are more commonly found among females as compared to males [ 69 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Polypharmacy was the most consistent and highly acknowledged predictor witnessed in almost all the literature to quantify the risk associated with ADR [1,15,24,[26][27][28][29]34]. In continuation, few studies quoted that polypharmacy is chosen when a patient presents with multiple comorbidities in order to augment the initial therapy and advanced age of patients who may require drugs with varied mechanisms of action [35]. However, polypharmacy intensifies the possibility of ADRs due to drug-drug interactions from 2% to 5% [36][37][38][39][40] and may heighten it up to 9% with each additional prescribed drug thereafter [27].…”
Section: Polypharmacymentioning
confidence: 99%
“…Moreover, females are known to use oral contraceptives, hormonal supplements adding on to increased number of drugs, especially in their reproductive years, and vitamin and mineral supplements during pre and postmenopausal periods that may predispose them for ADRs [55]. However, few studies recommended that it was not a significant risk factor of ADR through their observations [35,56].…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…La interacción puede aumentar o disminuir los efectos de los fármacos implicados y puede causar toxicidad inesperada, provocando una reacción adversa. Otros factores se relacionan con la comorbilidad, ya que si además de la enfermedad que se está tratando el paciente sufre otra enfermedad (como una alteración renal, hepática o cardiaca), se pueden requerir precauciones especiales para el tratamiento de las enfermedades intercurrentes y los fármacos concurrentes interactivos, especialmente cuando existen antecedentes de RAM en el paciente 4,5 .…”
Section: Introductionunclassified